Modeling human natural killer cell development and drug response in a microfluidic bone marrow model - Koenig, Leopold; Ben-Eliezer, Inbal; Tao, Thi Phuong; Winter, Annika; Grossman, Moran (Frontiers in Immunology, 2025)
IntroductionThe human bone marrow is a complex organ that is critical for self-renewal and differentiation of hematopoietic progenitor cells into various lineages of blood cells. Perturbations of the hematopoietic system have been reported to cause numerous diseases. Yet, understanding the fundamental biology of the human bone marrow in health and disease and during the preclinical stages of drug development is challenging due to the complexity of studying or manipulating the human bone marrow. Human cell-based microfluidic bone marrow models are promising research tools to explore multi-lineage differentiation of human stem and progenitor cells over long periods of time.MethodsHuman hematopoietic stem and progenitor cells were cultured with mesenchymal stromal cells on a zirconium oxide ceramic scaffold in a microfluidic device recapitulating the human bone marrow. NK cell differentiation was induced by the application of a lymphoid cultivation medium containing IL-15. The kinetics of differentiation into mature NK cells was traced by flow cytometry over a period of up to seven weeks, and functionality was measured by stimulation with phorbol myristate acetate (PMA) and ionomycin. The effect of an anti-IL-15 monoclonal antibody (TEV-53408) on different NK cell subtypes was tested at different time points.ResultsOur data shows that within 28 days of culture, differentiation into all developmental stages of NK cells was accomplished in this system. Alongside with the NK cells, myeloid cells developed in the system including granulocytes, monocytes and dendritic cells. The differentiated NK cells could be activated after stimulation with PMA and ionomycin indicating the functionality of the cells. Treatment with an anti-IL-15 antibody induced a reduction in proliferation of late-stage NK cells as shown by EdU staining. This led to significantly dose dependent reduction in the number of circulating stage 4 - 6 NK cells in the system after one week of treatment. This effect was partially reversible after a two-week treatment-free period.DiscussionIn summary, the presented model enables investigation of human NK cell development in the bone marrow and provides a basis to study related diseases and drug response effects in a microenvironment that is designed mimic human physiology.